Growth Charts for Prader-Willi Syndrome During Growth Hormone Treatment. (September 2016) - Butler, Merlin G.; Lee, Jaehoon; Cox, Devin M.; Manzardo, Ann M.; Gold, June-Anne; Miller, Jennifer L.; Roof, Elizabeth; Dykens, Elisabeth; Kimonis, Virginia; Driscoll, Daniel J.
The purpose of the current study was to develop syndrome-specific standardized growth curves for growth hormone–treated Prader-Willi syndrome (PWS) individuals aged 0 to 18 years. Anthropometric growth-related measures were obtained on 171 subjects with PWS who were treated with growth hormone for at least 40% of their lifespan. They had no history of scoliosis. PWS standardized growth curves were developed for 7 percentile ranges using the LMS method for weight, height, head circumference, weight/length, and BMI along with normative 3rd, 50th, and 97th percentiles plotted using control data from the literature and growth databases. Percentiles were plotted on growth charts for comparison purposes. Growth hormone treatment appears to normalize stature and markedly improves weight in PWS compared with standardized curves for non–growth hormone–treated PWS individuals. Growth chart implications and recommended usage are discussed.